Neurotoxicity, haemostatic disturbances and haemolytic anaemia after a bite by a Tunisian saw-scaled or carpet viper (Echis 'pyramidum'-complex): failure of antivenom treatment. - Gillissen, A; Theakston, R; Barth, J; May, B; Krieg, M; Warrell, D (1994)
A young man in Germany was bitten by a large captive saw-scaled viper (Echis 'pyramidum'-complex) of Tunisian origin. During the first few hours after the bite he developed evidence of disseminated intravascular coagulation and fibrinolysis, and bled spontaneously. Despite being given a total of 310 ml of three different Echis-specific antivenoms (together with large amounts of fresh frozen plasma and concentrated clotting factors), venom antigenaemia (measured by enzyme immunoassay) and coagulopathy persisted for more than 10 days, and he developed a haemolytic anaemia and mild renal dysfunction. Transient bilateral ptosis was attributed to envenoming. The venom of the snake responsible for the bite was immunologically distinct from that of Nigerian E. ocellatus and was clearly not neutralised by the three monospecific antivenoms which had been administered. This case is another illustration of the geographical variation in snake venoms and the need for pooling venoms from snakes from different parts of the geographical range in the preparation of antivenoms. Envenoming by North African Echis species may not be reversible by available antivenoms.